Opening Up Alternatives to Dominant Ideological Constructions of English Language Teaching in Malaysia. Issue 3 (3rd July 2019) - Idrus, Mohd Muzhafar; Ismail, Habibah; Abdullah, Hazlina; Baharun, Hazleena; Mat Saad, Noor Saazai; Darmi, Ramiaida; Puteh-Behak, Fariza; Harun, Haliza
ABSTRACT: This paper investigates the impact of the Common European Framework of Reference for Languages (CEFR) on the way English language teaching (ELT) is currently understood and practised in Malaysia. It presents a critical discourse analysis of newspaper texts in order to show how CEFR represents a form of Western-imposed globalisation that conflicts with local cultures and values. We argue that the newspapers construct a dominant discourse that promotes a vision of society that accords with CEFR–ELT implementation. Our aim is to contribute to the development of a counter-discourse that challenges the broader world-view underpinning ELT.